Advanced 4-chamber echocardiography techniques enable clinically matched precise characterization of heart disease progression in mice - Ege Kacira; Mariam F. Oueis; Nawal H. Tamimi; Sarah L. Sturgill; Xianyao Xu; Thomas J. Hund; Mark T. Ziolo; Yuchi Han; Isabelle Deschênes; Ji-dong Fu (Communications Medicine)
Abstract Background: Transthoracic echocardiography remains the primary non-invasive method for assessing cardiac function in clinical practice. However, technical challenges in acquiring accurate apical 4-chamber-long-axis (A4CLAX) views have historically limited mouse studies to left ventricle (LV) assessment using parasternal short-axis (SAX) M-mode imaging. Methods: To overcome this limitation, we developed an A4CLAX imaging approach for mice and performed a comparative analysis with established echocardiographic methods to assess cardiac function in healthy mouse hearts. To evaluate the utility of A4CLAX in detecting disease progression, we longitudinally monitored cardiac function of C57BL/6 N mice (male and female) following severe transverse aortic constriction (TAC), using both long-axis biplane (LAX-BP) and conventional SAX M-mode assays. Results: Here we show that LAX-BP echocardiography demonstrates volumetric accuracy comparable to cardiac magnetic resonance (CMR) and detects significant LV functional decline within the first week post-TAC–changes that are not clearly captured by M-mode imaging. Importantly, A4CLAX further enables clinically relevant Doppler assessments, allowing detection of mitral valve regurgitation, restrictive filling patterns, and desynchronized valve motion. It also facilitates right ventricle (RV) functional evaluation and improved atrial visualization, revealing progressive enlargement of the left atrial (LA) and left atrial appendage (LAA) associated with worsening diastolic function. Conclusions: The A4CLAX imaging approach provides clinically comparable, comprehensive echocardiographic evaluation in murine models and offers improved sensitivity for detecting subtle changes in cardiac performance during disease progression.